Investigation of correlation between cholesterol intake, apolipoprotein B and Parkinson’s disease related genes in guinea pigs feeding a high-fat diet containing cholesterol - Pinar Kacamak; Cigdem Elmas; Hatice Ayse Tokcaer Bora; Seniha Selcen Babaoglu Aydas (PLoS ONE, 2026)
Apolipoprotein B (Apo B), which is involved in the transport of cholesterol, is thought to be associated with neurodegenerative diseases such as Parkinson’s disease in addition to atherosclerosis and cardiovascular diseases. We aimed to investigate the possible correlation between cholesterol intake, Apo B and parkin RING domain-containing E3 ubiquitin protein ligase (PARKIN), phosphatase and tensin homologue (PTEN)-induced kinase 1 (PINK1) and α-synuclein (SNCA), which have an important role in Parkinson’s disease. Throughout the 12-week experiment, female and male guinea pigs in control group were fed a standard chow diet, while those in experimental group were fed a high-fat diet containing cholesterol. When histochemical findings were analysed at the end of our study, neuronal degeneration in the midbrain and brain cortex sections of the group of male guinea pigs fed a high-fat diet containing cholesterol was more pronounced compared to the other groups. In addition, significant differences were observed between the groups in terms of PARKIN expression levels (p = 0.030) in the brain tissues and the immunolabeling densities of PINK1 (p = 0.027), phospho(ser228)-PINK1 (p = 0.031), phospho(ser129)-SNCA (p < 0.000), and tyrosine hydroxylase (TH) (p = 0.033), particularly in the midbrain sections. Significant strong positive correlations (+0.5 < r<+1.0, p < 0.05) were observed in midbrain sections between phospho(Ser228)-PINK1 and TH immunolabeling and cholesterol (CHOL) levels, between phospho(Ser228)-PINK1 immunolabeling and low-density lipoprotein (LDL) levels, and between SNCA, phospho(Ser228)-PINK1, phospho(Ser129)-SNCA, and TH immunolabeling and high-density lipoprotein (HDL) levels. Our study demonstrated that a high-fat diet containing cholesterol was associated with significant changes in PARKIN gene expression and significant alterations in PINK1 protein levels in male guinea pigs in the experimental group.